A bailout approach: Transaxillary Impella implantation in toxic cardiomyopathy. (July 2014) - Khaliel, Feras; Moss, Emmanuel; Demers, Philippe; Bouchard, Denis
The femoral artery has been the traditional approach for implantation of the Impella left ventricular assist device. We describe the case of a young man with toxic (cocaine-related) cardiomyopathy, severe left ventricular dysfunction, and moderate mitral insufficiency who received a transfemoral Impella left ventricular assist device that was relocated to the right axillary artery due to uncontrolled femoral access bleeding. The patient immediately stabilized post-implantation and was successfully bridged to a full recovery 6 days later.